2021
DOI: 10.1111/pedi.13219
|View full text |Cite
|
Sign up to set email alerts
|

In vivo confocal microscopy study of corneal nerve alterations in children and youths with Type 1 diabetes

Abstract: Objective To determine whether children and youths with Type 1 diabetes (T1D) have early alterations of the corneal subbasal nerve plexus detectable with in vivo confocal microscopy (IVCM) and to investigate the role of longitudinally measured major risk factors for diabetes complications associated with these alterations. Methods One hundred and fifty children and youths with T1D and 51 age‐matched controls were enrolled and underwent IVCM. Corneal nerve fiber length (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
14
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 31 publications
3
14
0
Order By: Relevance
“… 18 Values were CNFL 9.86 mm/mm 2 , CNFD 16.7 n/mm 2 , CNBD 10.4 n/mm 2 , CTBD 16.7 n/mm 2 , and CNFrD 1.44, respectively (Image of nerves in cornea Figure 1C ). Compared to healthy controls, these values are low 19 indicating small fiber neuropathy.…”
Section: Case Presentationmentioning
confidence: 78%
“… 18 Values were CNFL 9.86 mm/mm 2 , CNFD 16.7 n/mm 2 , CNBD 10.4 n/mm 2 , CTBD 16.7 n/mm 2 , and CNFrD 1.44, respectively (Image of nerves in cornea Figure 1C ). Compared to healthy controls, these values are low 19 indicating small fiber neuropathy.…”
Section: Case Presentationmentioning
confidence: 78%
“…Corneal nerve fractal dimension (CNFrD) is a newly developed IVCM parameter obtained with employment of the latest version of ACCMetrics program [ 25 , 26 ]. CNFrD indicates the structural complexity of corneal nerve fibres, which could be useful as an alternative means to identify patients with neuropathies of various causes.…”
Section: Discussionmentioning
confidence: 99%
“…Inc.) were performed in both eyes and for each parameter the mean of right and left eyes measurements was calculated. All the examinations were performed by the same expert operator (TC) as previously described [ 5 , 6 ].…”
Section: Methodsmentioning
confidence: 99%
“…In recent years, two new ophthalmologic imaging techniques, Spectral domain-optical coherence tomography (SD-OCT) and In vivo confocal microscopy (IVCM), emerged for their ability to identify early neurodegenerative changes in retina and cornea of subjects with diabetes [ 4 ]. Concerning the evaluation of these early ocular changes during the pediatric age, we demonstrated that a significant impairment of the minimum neuroretinal rim width (MRW) of the optic nerve head (ONH) measured with SD-OCT and of the corneal subbasal nerve plexus (SBP) measured with IVCM is present in T1D children and adolescents compared with age and gender-matched controls [ 5 , 6 ]. Our results also showed that long-term glycometabolic control and blood pressure partially predicted the presence of early damage signs, in agreement with recent findings that recognized glycemic control and hypertension as major risk factors for DN development and progression [ 2 ].…”
Section: Introductionmentioning
confidence: 99%